Pengaruh Besarannya Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Nurdin Nurdin; Hardian Mursito; Munzir Munzir (Universitas Indraprasta PGRI, 2020)
This study aims to determine the compensation and working discipline besaranya on employee performance. Methods The study is a survey research. Subjects of this study as many as 50 employees were taken randomly at PT. Lifes Good in Jakarta. Data was collected by questionnaires using Likert skla. The validity of the data obtained with the validity and reliability, all data has a normal distribution. The results showed that the compensation to give a significant influence on employee performance. Likewise, work discipline gives a significant influence on employee performance. The coefficient of determination (R) 2 is the compensation and working discipline has a strong relationship to employee performance.